QUALITATIVE DETERMINATION OF HERBAL OILS USED IN VARIOUSHERBAL AND COSMECEUTICALS FORMULATION - Kaneez Fatima et al (Baqai Journal of Health Sciences)
The object of present study is to analyze the various oils used in the preparation of herbal formulations and available in the market. However, it is uncertain whether these raw materials comply with the standards prescribed in the pharmacopeias. Methods In this study three oils of plant source i.e.Syzygium aromaticum, and .have been obtained from the market and various quality control tests including Physico-chemical characteristics, thin layer chromatography (TLC), spectrophotometric assay (British Pharmacopoeia) have been performed to determine their compliance with the officials standards. The TLC has been used for the identification of the active ingredients on comparison of their RF values with the reference standard. Result The qualitative and quantitative evaluation has been carried out on the selected herbal oils. Some of them were found to comply with official standards while some did not comply probably due to adulteration or being spurious or substandard raw material. Though this type of study provide useful data that would be helpful for manufacturer in the authentication of these oil obtained from plant sources for formulation purpose.